Unraveling the Mystery About the Negative Valence Bias: Does Arousal Account for Processing Differences in Unpleasant Words? - Vieitez, Lucía; Haro, Juan; Ferré, Pilar; Padrón, Isabel; Fraga, Isabel (Frontiers in Psychology, 2021)
Many studies have found that the emotional content of words affects visual word recognition. However, most of them have only considered affective valence, finding inconsistencies regarding the direction of the effects, especially in unpleasant words. Recent studies suggest that arousal might explain why not all unpleasant words elicit the same behaviour. The aim of the present research was to study the role of arousal in unpleasant word recognition. To do that, we carried out an ERP experiment in which participants performed a lexical decision task that included unpleasant words which could vary across three levels of arousal (intermediate, high, and very high) and words which were neutral in valence and had an intermediate level of arousal. Results showed that, within unpleasant words, those intermediate in arousal evoked smaller LPC amplitudes than words that were high or very high in arousal, indicating that arousal affects unpleasant word recognition. Critically, arousal determined whether the effect of negative valence was found or not. When arousal was not matched between unpleasant and neutral valenced words, the effect of emotionality was weak in the behavioural data and absent in the ERP data. However, when arousal was intermediate in both unpleasant and neutral valenced words, larger EPN amplitudes were reported for the former, pointing to an early allocation of attention. Interestingly, these unpleasant words which had an intermediate level of arousal showed a subsequent inhibitory effect in that they evoked smaller LPC amplitudes and led to slower reaction times and more errors than neutral words. Our results highlight the relevance that the arousal level has for the study of negative valence effects in word recognition.